Phase I/II study of carboplatin plus nab-paclitaxel and concurrent radiotherapy for patients with locally advanced non–small cell lung cancer. (November 2018) - Kawano, Yuko; Sasaki, Tomonari; Yamaguchi, Hiroyuki; Hirano, Katsuya; Horiike, Atsushi; Satouchi, Miyako; Hosokawa, Shinobu; Morinaga, Ryotaro; Komiya, Kazutoshi; Inoue, Koji; Fujita, Yuka; Toyozawa, Ryo; et al.
Highlights: Nab-paclitaxel at 50 mg/m 2 in concurrent phase was determined to be the RD. Common toxicities of grade 3 or 4 in concurrent phase was leukopenia and neutropenia. The ORR was 76.8% and mPFS was 11.8 months in 56 patients treated at the RD. Our results reveal encouraging feasibility and activity for this regimen. Abstract: Objectives: Chemoradiation regimens of greater efficacy are needed for patients with locally advanced non–small cell lung cancer (NSCLC). Patients and methods: In a phase I study, escalating doses of weekly nab-paclitaxel (40 or 50 mg/m 2 ) were administered along with weekly carboplatin at an area under the curve (AUC) of 2 mg mL –1 min and concurrent radiotherapy with 60 Gy in 30 fractions to patients with locally advanced NSCLC. This concurrent phase was followed by a consolidation phase consisting of two 3-week cycles of nab-paclitaxel plus carboplatin. In a phase II study, nab-paclitaxel was administered at the recommended dose (RD) together with carboplatin and radiation. Results: In the phase I study, one of six patients experienced dose-limiting toxicity (leukopenia of grade 3 requiring a second consecutive skip in the administration of weekly chemotherapy) with nab-paclitaxel at 50 mg/m 2, which was therefore determined to be the RD. Fifty-six patients treated at the RD were evaluable for safety and efficacy. Common toxicities of grade 3 or 4 in the concurrent phase included leukopenia (60.7%) and neutropenia (28.6%). No treatment-related deaths occurred during the study period. The objective response rate was 76.8% (95% confidence interval [CI], 64.2–85.9%), median progression-free survival was 11.8 months (60% CI, 10.6–16.2 months; 95% CI, 8.2–20.8 months), and median overall survival was not reached. Conclusion: Our results reveal encouraging feasibility and activity for concurrent chemoradiation with nab-paclitaxel at 50 mg/m 2 and carboplatin at an AUC of 2 in patients with locally advanced NSCLC.